방문 돌봄 노동자의 근골격계 자각증상, 수면문제와 주관적 정신건강 간의 관련성 : 수면문제의 매개효과를 중심으로 - 양주현; 이은정; 정인옥; 박보현 (한국직업건강간호학회지, 2022)
Purpose: This study aimed to identify the relationship among musculoskeletal problems, sleep problems, and self-rated mental health of home-care workers. Methods: Data were collected from 447 home-care workers spanning three occupation types: life supporters for the elderly, home-visit caregivers, and life supporters for the disabled. Musculoskeletal problems, sleep problems, and self-rated mental health were assessed using structured questionnaires. Factors affecting self-rated mental health were analyzed using multiple regression. SPSS was used to test the mediating effects of sleep problems on musculoskeletal problems and self-rated mental health. Results: Among the general characteristics, the variables that showed significant differences in musculoskeletal problems were monthly income level, caring-related career duration, weekly working hours, and occupation type; and the variable that showed significant differences in self-rated mental health was occupation type. Among the occupation types, supporters for the disabled had the most musculoskeletal problems and the lowest self-rated mental health. Musculoskeletal problems among home-care workers had a direct negative effect on self-rated mental health and indirect negative effects on sleep problems. Conclusion: Measures are needed to reduce the differences in working conditions and health status among the occupation types of home-care workers. Considering the relevance between the health issues of home-care workers, the development of a carefully designed health promotion strategy is required.